PEMBERDAYAAN UKM BATIK SENG DESA SENGGURUH KABUPATEN MALANG - Triatmanto, Boge; Sanusi, Anwar; Siswati, Aris (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2019)
Batik is one of the original types of Indonesian culture, even UNESCO has determined Batik as one of the world's cultural heritages. In its development came a variety of batik motifs including the ways or processes used in producing batik. Indonesia recognizes batik as a form of art work done by humans by giving certain patterns to plain cloth by waxing wax to block color, which is what is known as batik cloth. The making of written batik requires special expertise because the process must be carried out through certain stages. The quality of the finished batik cloth is very dependent on the skills of batik craftsmen to go through each stage of the batik process. Sengguruh Village, Malang Regency has a Batik Written UKM which has quite potential to develop its business. But the lack of the number of crafters possessed is an obstacle in producing written batik. Another obstacle experienced is the lack of understanding of written batik craftsmen to each stage of the process that must be passed. The results of the written batik SOP training provide new knowledge and provide deeper understanding to the batik crafters, so that when the batik process is passed well it will produce batik cloth which is also better in quality.